Can flipped learning enhance adolescents' motivation in physical education? An intervention study - Ove Østerlie (Cappelen Damm Akademisk NOASP, 2018)
Objective: To be engaged and successful in learning in physical education (PE), students needs to be motivated. The purpose of this study was to examine the impact of flipped learning (FL) on adolescents' motivation to participate in PE. Methods: Students in Grades 8-11 (N = 338, 45.3% girls) were recruited from 6 secondary and upper-secondary schools from three different counties in Norway in the spring semester of 2016. Following a quasi-experimental design with a control group, data were gathered using an expectancy-value questionnaire (EVQ). Results: Mean results revealed that FL has a significant impact on adolescents' expectancy beliefs and attainment values regarding participation in PE. All significant changes in the intervention group could be explained by gender. Conclusion: In an expectancy-value perspective, FL positively influences the motivation of adolescents, especially that of girls, to participate in PE. Therefore, FL can be used to enhance adolescents' motivation to participate in PE.